2016
DOI: 10.1080/01677063.2016.1202950
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of axonal transport defects inDrosophilaHuntingtin mutants

Abstract: Polyglutamine (polyQ) expansion within Huntingtin (Htt) causes the fatal neurodegenerative disorder Huntington’s Disease (HD). Although Htt is ubiquitously expressed and conserved from Drosophila to humans, its normal biological function is still being elucidated. Here we characterize a role for the Drosophila Htt homolog (dHtt) in fast axonal transport (FAT). Generation and expression of transgenic dHtt-mRFP and human Htt-mRFP fusion proteins in Drosophila revealed co-localization with mitochondria and synapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 49 publications
0
15
1
Order By: Relevance
“…1B). Thus, data from the type Is motoneuron terminal differ from findings previously obtained in axons of CCAP-containing peptidergic neurons (Weiss and Littleton, 2016). Furthermore, tracking of DCVs through photobleached proximal boutons showed that Htt KO does not affect DCV transport velocity: for anterograde transport, DCVs moved at 0.89 ± 0.09 μm/s in controls and 0.93 ± 0.10 μm/s in Htt KOs, while for retrograde transport, DCVs moved at 0.81 ± 0.07 μm/s in controls and 0.83 ± 0.08 μm/s in Htt KOs (Control, n = 13; Htt KO, n = 16).…”
Section: Resultscontrasting
confidence: 77%
See 2 more Smart Citations
“…1B). Thus, data from the type Is motoneuron terminal differ from findings previously obtained in axons of CCAP-containing peptidergic neurons (Weiss and Littleton, 2016). Furthermore, tracking of DCVs through photobleached proximal boutons showed that Htt KO does not affect DCV transport velocity: for anterograde transport, DCVs moved at 0.89 ± 0.09 μm/s in controls and 0.93 ± 0.10 μm/s in Htt KOs, while for retrograde transport, DCVs moved at 0.81 ± 0.07 μm/s in controls and 0.83 ± 0.08 μm/s in Htt KOs (Control, n = 13; Htt KO, n = 16).…”
Section: Resultscontrasting
confidence: 77%
“…In addition, Htt scaffolds GAPDH (glyceraldhyde 3-phosphate dehydrogenase) on vesicles and Htt depletion induces detachment of GAPDH from vesicles leading to decreased axonal transport of BDNF and APP (Zala et al, 2013b). Finally, Htt may induce secondary effects on axonal transport by regulating dynein heavy chain expression (Weiss and Littleton, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HAP1 also interacts with the p150 Glued subunit of dynactin (Li et al, 1998;Engelender et al, 1997), as well as the kinesin heavy chain and light chain (Twelvetrees et al, 2010;McGuire et al, 2006), implicating the two proteins as having a role in intracellular transport (Block-Galarza et al, 1997). While huntingtin has been linked to the axonal transport of several vesicle populations (Wong and Holzbaur, 2014;Gunawardena et al, 2003;Weiss and Littleton, 2016;Colin et al, 2008;Her and Goldstein, 2008), HAP1 is required for the huntingtin-mediated transport of autophagosomes (Wong and Holzbaur, 2014), as well as for APP trafficking (Yang et al, 2012). It has been suggested that huntingtin and HAP1 together act as a platform for both dynein and kinesin attachment to vesicles (Box 1), although the large size of the complex has made it difficult to dissect the underlying mechanisms through in vitro assays.…”
Section: Candidate Activatorsmentioning
confidence: 99%
“…Cargo type should thus be considered and the aims of each individual experiment carefully determined before selecting from the following analysis options, which may also be subdivided into anterograde, retrograde, bi-directional, and combined categories: Speed Frequency of frame-to-frame speeds ( Figure 1Ci ) 11 , 67 , 70 , 71 Individual cargo average velocities ( Figure 1Cii ) 71 Average 52 , 56 , 71 , 92 and maximum cargo speeds ( Figure 1Ciii ) 71 Immobile cargoes can be either included or omitted, and analysed separately 59 , while movement-only speeds (i.e. uninterrupted runs or constant-velocity segments) can be determined 52 , 92 Motility Percentage 14 , 35 , 45 and number 20 , 52 , 56 , 92 of motile cargoes in a given time (also called flux) Percentage of time motile cargoes are moving 12 , 60 Average 56 and longest 45 run distances (run length) Run duration 12 , 13 , 39 Pausing Percentage of cargoes that pause ( Figure 1Civ ) 67 , 71 Percentage 21 , 71 and length 52 , 77 , 92 of time that motile cargoes remain stationary ( Figure 1Cv ) Pause frequency 52 ...…”
Section: Assessment Of Cargo Motility In Axons From An Array Of Zebramentioning
confidence: 99%